Functional and structural studies of the flavivirus RNA-dependent RNA polymerase - Yap, Thai Leong (2009)
Dengue fever, a neglected emerging disease for which no vaccine or antiviral agents exist at present, is caused by dengue virus, a member of the Flavivirus genus. The NS5 protein from dengue virus (DENV) is bi-functional and contains 900 amino acids. The S-adenosyl methionine transferase activity resides within its N-terminal domain, and residues 270 to 900 form the RNA-dependent RNA polymerase (RdRp) catalytic domain. Viral replication begins with the synthesis of minus-strand RNA from the dengue virus positive-strand RNA genome, which is subsequently used as a template for synthesizing additional plus-stand RNA genomes. This essential function is catalyzed by the NS5 RdRp and thus the protein represents an interesting target for the development of specific antiviral compounds. Therefore, this work set out to investigate the structural basis of DENV RdRp in order to provide clues to understand the molecular details of its role and function in viral genome replication. This thesis work presents three aspects of study that consists: (1) the protein expression strategy and characterization of NS5 polymerase, (2) a multi-step strategy to obtain crystal of DENV RdRp for high resolution diffraction and soaking studies and (3) structural insight of the DENV RdRp. To obtain soluble proteins for structural and functional studied, an extensive array of approaches has been explored, which comprises (1) expression hosts and conditions, (2) refolding, (3) limited proteolysis and (4) homologous protein screening. The enzymatic activity shows that the RdRp domain is less active than the full length (FL) NS5, which is also supported insights from the limited proteolysis experiments and Fab epitope mapping. The limited proteolysis results indicate that the catalytic domain RdRp protein adopts a more open and flexible conformation than the FLNS5.Antibody Fab fragments that were obtained in this study and found to recognize conformational epitope interacted more weakly with the RdRp domain compared with the FLNS5. Together these two approaches imply conformational difference between the RdRp and FLNS5 that possibly account for the difference in activity. For structural studies, a very intensive campaign to crystallize the FL protein has been attempted in this working using proteins expressed from both insect baculovirus expression system and E.coli expression. NS5 from two different strains belonging to serotype 2 and WNV were investigated. Complex of NS5 with Fab fragment and also NS3 were investigated for crystal production. In parallel, truncated constructs expressing various parts of NS5 were also exhaustively studied with the information gleaned from limited proteolysis. These studies led to the first successful crystallization of a DENV RdRp from serotype 3. Initially the crystals diffracted poorly were markedly improved by the addition of divalent metal ions and air hydration, whichled to crystals with high resolution diffraction (1.85 A) thus making is possible to use molecular replacement to solve the structure.